A Literature Review of Effect of Moringa Oleifera Leaf Extract Toward Lipid Profile Level in Hyperlipidemia Patients - Arwani; Waode Fitrah Sari; Suwondo, Ari (Alta Dharma Publisher, 2022)
Background: Hyperlipidemia is a lipid disorder characterized by increased total serum cholesterol, LDL (Low-Density Lipoprotein), triglycerides, and a decrease in HDL levels. Objective: This research aims to identify the effectiveness of Moringa oleifera leaf extract on lipid profile levels (total cholesterol, LDL, HDL, and triglycerides) in hyperlipidemic patients. Method: The research design of a Systematic Literature Review was done by identifying, evaluating, and interpreting all available relevant research, especially on problem formulation. The journal search process was done by screening, assessing journal quality, analysis, and conclusions. Results: That process obtained 25 national and international journals. Then, the writer's analysis concluded that Moringa oleifera leaf extract was more effective in increasing HDL levels with a yield of 34% and lowering LDL levels with a journal yield of 24%. On the other hand, giving Moringa oleifera leaf extract was less effective in reducing total cholesterol and triglyceride levels in the blood by a 21% yield percentage. Conclusion - The intervention effectiveness of Moringa oleifera leaf extract is effective in increasing HDL serum (High-Density Lipoprotein) levels and decreasing LDL serum (Low-Density Lipoprotein) levels in hyperlipidemic patients. Recommendation: The author recommends other researchers examine the effectiveness of giving moringa leaf extract in liquid dosage forms and Moringa leaf extract in powder or powder with doses of moringa leaf extract of 300mg/kg-BW and 700 mg/kg-BW for more than 14 days